2013
DOI: 10.1007/s00586-013-2783-8
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for surgical site infection of spinal instrumentation surgery for diabetes patients

Abstract: Purpose Diabetes mellitus (DM) is known as an important risk factor for surgical site infection (SSI) in spine surgery. It is still unclear however which DM-related parameters have stronger influence on SSI. The purpose of this study is to determine predisposing factors for SSI following spinal instrumentation surgery for patients with DM. Methods 110 DM patients (66 males and 44 females) who underwent spinal instrumentation surgery in one institute were enrolled in this study. For each patient, various preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
1
36
0
1
Order By: Relevance
“…In patients with diabetes mellitus, local changes in the tissues, along with neuropathy and angiopathy, increased the risk of infection. Previous studies reported that patients with poorly regulated blood glucose levels had a 10% -20.9% SSI rate (9,16,20). Our study supported these results.…”
Section: Risk Factors For Postoperative Infectionsupporting
confidence: 91%
“…In patients with diabetes mellitus, local changes in the tissues, along with neuropathy and angiopathy, increased the risk of infection. Previous studies reported that patients with poorly regulated blood glucose levels had a 10% -20.9% SSI rate (9,16,20). Our study supported these results.…”
Section: Risk Factors For Postoperative Infectionsupporting
confidence: 91%
“…3-5 In patients with DM who underwent degenerative lumbar spine surgery, studies have shown reduced pain improvement, increased incidence of fusion complications and increased incidence of surgical site infections relative to those patients without DM. 4-6 A recent study from 2011, comparing patient centered outcomes in diabetics versus non-diabetics undergoing surgical intervention for common degenerative spinal diseases, showed some pain improvement following treatment of spinal stenosis and degenerative spondylolisthesis but no improvement following treatment of intervertebral disc (IVD) herniation. 7 However, this study did not stratify patients between varying levels of glycemic control, making it impossible to determine whether the severity of a patient’s diabetic condition also influenced surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of intraoperative blood loss is associated with higher rates of SSIs, for example, in lumbar fusion, 37 in pediatric patients, 38 and in diabetic patients. 39 In the DG we observed a higher blood loss (p ¼ 0.025) compared with the nDG. However, the subgroup of patients in the DG with SSIs showed no significant differences in blood loss (p ¼ 0.977) compared with the nDG.…”
Section: Surgical Site Infectionmentioning
confidence: 62%